The Roman Villa in Eretz Israel: A Solution for Agrarian and Historical Problems - Dar, Shimon (Liber Annuus, 2021)
Abstract For many years the problem of the Roman Villa in the Land of Israel was an enigma. In 1987 the late Prof. Shimon Applebaum wrote a paper asking the question: If the Villa was a sign of Roman culture in the provinces, why is the evidence in the Land of Israel so meager? The Roman Villa is well known in Italy and especially in the Western Provinces, from historical sources and Archaeology. In Eretz Israel the local farmhouse was abundant, dating from Iron Age 2 till the Byzantine Period. But the Roman style Villa was very rarely discovered in Archaeological excavations. No example was comparable to the typical Roman Villa. After many years of field work in Western Samaria, we concluded that in Eretz Iarael the local farmhouse was different from the Roman Villa, but the reasons were not then clear. New excavations in the last generation solved the enigma: After the two revolts against Rome (67-73 AD; 132-136 AD) and especially after the Bar Kokhba revolt, the Roman empire confiscated the Jewish territory and leased it, probably to gentiles (Josephus, War 7,6,6). The Jewish farmers and their farmhouses which took part in the revolts, were destroyed. In this paper we count many sites, stretching from lower Galilee, Mount Carmel, the Jerusalem and Hebron mountains from which we have evidence for the phenomena. The Roman Imperial Administration established some military veterans’ settlements, but most of the Jewish farms were deserted for a couple of generations, until loyal Roman settlers were granted the farms and the lands. Those farms, settled by gentiles, existed until the Byzantine period.